Response of soft tissues and abdominal organs of rabbits and rats to implanting albucid-containing cross-linked polyurethane composite - N. A. Galatenko; R. A. Rozhnova; D. V. Kuliesh; T. V. Visloguzova; A. P. Maletskyy; N. M. Bigun (Ukrainian Society of Ophthalmologists, 2020)
Background: Craniofacial injuries represent 29% of all trauma cases, and patients need to have their affected orbit, orbital adnexa, and periorbital area surgically reconstructed or restored. However, the outcomes of these procedures depend also on the quality of implant materials. Previously, we have developed a polymer material made of cross-linked polyurethane (PU) and containing a biologically active substance, albucid; it seems to be a promising implant material. Purpose: To investigate experimentally the response of soft tissues and abdominal organs of animals (rabbits and rats) to implanting the albucid-containing cross-linked PU composite. Material and Methods: Assessment of soft tissue response to implantation of the synthetic polymer material. The skin response to implanting the albucid-containing cross-linked PU composite was assessed through the intracutaneous injection of the extract of the test material in rabbits. The soft tissue response was assessed through subcutaneous implantation of cross-linked PU composites in Wistar rats. The response of abdominal organs to implanting the cross-linked PU composite was assessed through the intraperitoneal injection (20 ml per kg body weight) of the extract of the test material in Wistar rats. Conclusion: The intracutaneous injection of the extract of the test material caused neither erythema nor edema in rabbits, and the test sample of the albucid-containing cross-linked PU composite was considered non-irritating, since a difference between the average scores for the test extract and control extract (i.e., a value of the primary irritation index) was of 0 to 0.4 points. Over the period of observation of potential acute systemic toxicity, no animal injected with the extract of the test material (the albucid-containing cross-linked PU composite) displayed higher biologic response than animals injected with the control extract, and the test sample of the albucid-containing cross-linked PU composite conformed to the requirements of tests for systemic toxicity. This study demonstrated a natural process for a foreign body residing in the body (gradual foreign body separation from the surrounding tissues due to formation of a connective tissue capsule) after implantation of the samples of cross-linked PU composites in animal bodies. The cellular responses were (1) typical for a living body response to the presence of a foreign body at the site of implant placement and (2) characteristic for aseptic inflammation. The test samples produced moderate irritation when placed into the animal's body.